Research on Improving Camshift Algorithm about Target Tracking - QIN Yong; SHANG Meng-meng; ZHAO Xiao-hong; GAI Jian-xin (Journal of Harbin University of Science and Technology)
The target is easily lost by using Camshift when the target is blocked or accelerated in complex background. The reason for this is Camshift is an algorithm that uses color characteristics to track the target. For solving above shortcomings, the improving Camshit algorithm is proposed in this paper. Firstly, the search window is automatically selected using frame difference method. Then, the weighted color histogram is introduced to eliminate the interference of similar background colors. Finally, the accelerating object can be tracked accurately based on Camshift algorithm combined with Kalman filter prediction. It is shown with experimental data that the blocked or accelerating target can be accurately located by used the method proposed in this paper.